Perancangan Video Promosi Kopi G’royal Kerinci - fariz, idlal; M. Sayuti (TRADISIGN : Jurnal Pustaka Desain dan Budaya, 2024)
In designing the promotional video for G’Royal Kerinci coffee, a qualitative descriptive approach and the 4D method were used to produce an effective and engaging video. The qualitative descriptive approach aims to gather in-depth information about G’Royal Kerinci coffee through interviews with farmers, coffee processors, baristas, and consumers, as well as direct observation of the production process and local culture in Kerinci. This observation includes stages of production from planting, picking, processing, to packaging coffee, and observing the surrounding environment and culture that influence the quality and characteristics of the coffee. Additionally, document analysis from various reports and articles documenting the history and quality of G'Royal Kerinci coffee provides further insights. The 4D method (Define, Design, Develop, Disseminate) is used to systematically design and implement the promotional video. The Define stage involves identifying the purpose of the video, which is to increase awareness and sales of G'Royal Kerinci coffee, as well as defining the target audience such as premium coffee lovers, millennials, and young professionals. In the Design stage, the video’s concept and theme are crafted to reflect the uniqueness and quality of G'Royal Kerinci coffee, accompanied by the creation of a storyboard and script that outlines the storyline, visuals, and narration of the video. The Develop stage involves video production with shooting in coffee plantations, processing plants, and coffee shops, as well as video editing by adding background music, narration, and visual effects to create an appealing and professional video. Finally, in the Disseminate stage, the video is launched on various platforms such as YouTube, Instagram, and the company’s website, supported by promotional strategies through social media, paid advertisements, and email marketing to reach a wider audience. This approach results in an informative promotional video that successfully captures the audience’s attention towards G'Royal Kerinci coffee.